PERANGKAT PEMBELAJARAN BAHASA ARAB YANG BERKARAKTER DAN BERBUDAYA YANG BERBASIS KTSP PADA SISWA KELAS VII MTs NEGERI KENDAL (Lisanul Arab: Journal of Arabic Learning and Teaching, 2012)
The Government has launched the implementation of the nation's culture and character education for all levels of education. Development of culture and national character are integrated into the subject, ie the values of culture and national character education integrated into the curriculum, syllabus and Teaching Implementation Plan (RPP) which already exists. But unfortunately, the integration of cultural values and national character is not yet fully understood all educators. In addition, learning Arabic in the classroom is still limited to a transfer course materials, directed only at the cognitive and psychomotor, not to the affective domain. Learning is not directed at the formation of the attitude and personality of the students which is a form of integration of cultural values and national character education in learning. This study aimed to describe the character of learning Arabic and cultured in class VII MTs N Kendal and describe the implementation of Arabic language learning device that character and those cultured in the classroom.